Answer:
y = -6
x = 1
Step-by-step explanation:
-x + 2y = -13
-x - 2y = 11
Sum the equations:
-x -x = -2x
+2y - 2y = 0
-13 + 11 = -2
then
-2x = -2
x = -2/-2
x = 1
from the first eq.
-x + 2y = -13
-1 + 2y = -13
2y = -13 + 1
2y = -12
y = -12/2
y = -6
check:
from the second eq.
-x -2y = 11
-1 -(2*-6) = 11
-1 -(-12) = 11
-1 + 12 = 11
Answer:
120÷5=24 / 24×4=96 / 96+24=120
Step-by-step explanation:
Answer:
The distributive property is one of the most frequently used properties in math. In general, this term refers to the distributive property of multiplication which states that the. Definition: The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.
Answer:
i wonder why
Step-by-step explanation:
Answer: you minus the equations you have to get the equation that you want so it all can add up to that *
Step-by-step explanation: